2015
DOI: 10.1161/circep.114.002162
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Mechanisms for Cardiac-Specific MicroRNAs and cAMP Signaling in Electrical Remodeling

Abstract: Background Loss of transient outward K+ current (Ito) is well documented in cardiac hypertrophy and failure both in animal models and humans. Electrical remodeling contributes to prolonged action potential duration (APD) and increased incidence of arrhythmias. Furthermore, there is a growing body of evidence linking microRNA (miR) dysregulation to the progression of both conditions. In this study, we examined the mechanistic basis underlying miR dysregulation in electrical remodeling and revealed a novel inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In our previous study we showed that cardiomyocyte-specific inactivation of the cAMP-dependent transcriptional activator CREB leads to AP prolongation due to an I to reduction likewise along a decrease of Kcnd2 mRNA and Kv4.2 protein in VCMs [ 34 ]. Our own results are supported by a recent study that postulates ICER as a repressor of Kcnd2 /KV4.2/ I to by repressing miR-1 [ 28 ]. Hence, data from three independent mouse models strongly suggest that inactivation or repression of cAMP-dependent transcription leads to I to remodeling.…”
Section: Discussionsupporting
confidence: 86%
“…In our previous study we showed that cardiomyocyte-specific inactivation of the cAMP-dependent transcriptional activator CREB leads to AP prolongation due to an I to reduction likewise along a decrease of Kcnd2 mRNA and Kv4.2 protein in VCMs [ 34 ]. Our own results are supported by a recent study that postulates ICER as a repressor of Kcnd2 /KV4.2/ I to by repressing miR-1 [ 28 ]. Hence, data from three independent mouse models strongly suggest that inactivation or repression of cAMP-dependent transcription leads to I to remodeling.…”
Section: Discussionsupporting
confidence: 86%
“…Enhanced expression of the cAMP early repressor suppressed the expression of miR-1 and miR-133a, leading to hypertrophy and electrical remodeling, respectively. Meanwhile, by delivering miR-1 and miR-133a in vivo , inducible cAMP early repressor expression was blocked so that both hypertrophy and electrical remodeling were alleviated (Myers et al, 2015 ). Therefore, feedback mechanisms for cardiac-specific miR133a, miR-1, and cAMP signaling pathways exist in cardiac hypertrophy and electrical remodeling, providing proof-of-concept for the potential applications of miR-1 and miR-133a therapy for MI.…”
Section: The Roles Of Mir-133 In Cardiac Remodelingmentioning
confidence: 99%
“…Hyperpolarization-activated non-specific cation channels (HCNs) conduct a mixed K + /Na + depolarizing current, which is activated by cAMP and hyperpolarization. Once the HCNs are activated in the myocardial diastolic period, membrane depolarization is triggered immediately (Myers et al, 2015 ; Wen and Li, 2017 ). In the right atrial appendage from patients with AF, the levels of HCN2 and HCN4 channels are significantly increased, accompanied by a decrease in miR-133 and miR-1 levels with aging.…”
Section: The Roles Of Mir-133 In Cardiac Remodelingmentioning
confidence: 99%
“…Recent technical developments in 'omics' technologies promise to be at the forefront of this field. At the gene level, next generation gene sequencing technologies have led to the identification of microRNAs and long non-coding RNAs (lncRNAs) that play critical roles in regulating transcription and translation of many genes, including ion channel genes (Greco & Condorelli, 2015;Myers et al 2015). At the protein level, new mass spectrometry methods have enabled global analyses of integrated responses rather than the analysis of individual components (Ferreira et al 2015).…”
Section: Mechanisms Of Cardiac Electrical Remodelling In Acquired Dismentioning
confidence: 99%